Labor migration in Russia during the coronavirus pandemic - Mikhail Denisenko; Vladimir Mukomel (Демографическое обозрение, 2021)
The introduction of quarantine measures in connection with the coronavirus pandemic was accompanied by the blocking of cross-border communications and the restriction of the activities of enterprises in most sectors of the economy. Labor migrants and members of their families staying on the territory of Russia found themselves in a difficult situation. The decline in employment, primarily in those areas where migrants work, has made foreign citizens one of the most vulnerable social groups. The first layer of issues considered in the article is associated with an assessment of the situation in which migrants have found themselves in Russia. In what types of    economic activity has the decline in employment become particularly painful for migrants? What is their financial situation? To what extent are they ready to leave Russia if transport communications are restored? What are their immediate and long-term plans related to work and life in Russia? The second focus of the study is on potential migrants who were unable to enter Russia after the severance of international transport links. What is their economic situation at home? How quickly are they going to leave for Russia if restrictions on international travel are lifted? What are their short-term and long-term plans related to their stay in Russia? This article is devoted to finding answers to these questions, based on an online survey of 2,695 foreign citizens (including 1,304 migrants located in Russia and 1,391 abroad), as well as a telephone survey of 300 labor migrants in the Moscow metropolis conducted in the first half of June 2020.